AVERAGE D-DISTANCE BETWEEN VERTICES OF A GRAPH - Babu, D. Reddy; Varma, P.L.N. (Italian Journal of Pure and Applied Mathematics, 2014)
The D-distance between vertices of a graph G is obtained by considering the path lengths and as well as the degrees of vertices present on the path. The average D-distance between the vertices of a connected graph is the average of the D-distances between all pairs of vertices of the graph. In this article we study the average D-distance between the vertices of a graph.